Simultaneous Temporal Interval Production and Duration Discrimination in Practised Subjects - Brewster, Martha Joan (My University, 1983)
Theories of the perception of short time intervals have generally postulated a single timing mechanism which serves in all experimental situations, including both duration discrimination and interval production. Despite this hypothesis, the characteristics of timing behaviour are not always the same for different timing tasks.
A dual timing task was devised, in which subjects concurrently perform both response-stimulus synchronization and duration discrimination. They were required to discriminate the time of occurrence of a brief auditory stimulus presented during a 460-msec, synchronization interval, also marked by brief auditory stimuli. The internal interval produced to perform response-stimulus synchronization can be deterministic and, if this interval could be used as a criterion for duration discrimination in the dual task, "perfection" discrimination might result. This end was not attained but both synchronization and duration discrimination were performed as well concurrently as they are when they are performed separately. The independence of the variability found in the two tasks suggests that they may not be accomplished by the same timing mechanism.
Although performances on the concurrent tasks were largely independent, the stimuli marking the duration discrimination interval had systematic effects on synchronization performance. A qualitative model was proposed to account for these effects. When stimuli are expected during the synchronization interval, the produced interval is occasionally interrupted, until the stimulus is observed. The momentary discontinuities, each of which adds a small amount of time to the final response, occur within a temporal "observation window" which is established after experience with a particular stimulus set.
The variances of the two concurrent tasks were independent, indicating that a single timing mechanism will not easily account for behaviour in all situations involving the timing of brief intervals. However, the systematic effects of the duration discrimination stimuli on synchronization behaviour suggest that the two tasks do share some processing resources.
Keywords: Psychology; Psychology